2020
DOI: 10.1016/j.esxm.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Four Polymorphisms Located at the Promoter of the Estrogen Receptor Alpha ESR1 Gene in a Population With Gender Incongruence

Abstract: Introduction Gender incongruence defines a state in which individuals feel discrepancy between the sex assigned at birth and their gender. Some of these people make a social transition from male to female (trans women) or from female to male (trans men). By contrast, the word cisgender describes a person whose gender identity is consistent with their sex assigned at birth. Aim To analyze the implication of the estrogen receptor α gene ( ESR1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…According to Table 1, E1 measurements could be relevant during oral E2 treatment, but this hypothesis remains to be tested. Recently, polymorphisms of the estrogen receptor α gene were associated with gender incongruence in transgender men, whereas no association was found in transgender women (106). In postmenopausal women, variations in the estrogen receptors affected individual variation in treatment effects of E2 (107), and further studies regarding variations in the estrogen receptor are requested in transgender study populations.…”
Section: Monitoring Gaht In Transgender Carementioning
confidence: 99%
“…According to Table 1, E1 measurements could be relevant during oral E2 treatment, but this hypothesis remains to be tested. Recently, polymorphisms of the estrogen receptor α gene were associated with gender incongruence in transgender men, whereas no association was found in transgender women (106). In postmenopausal women, variations in the estrogen receptors affected individual variation in treatment effects of E2 (107), and further studies regarding variations in the estrogen receptor are requested in transgender study populations.…”
Section: Monitoring Gaht In Transgender Carementioning
confidence: 99%
“…Most studies about the genetic basis of GI analyzed the implication of some DNA polymorphisms related to ERs, α and β, the AR, the aromatase CYP19A1 or the CYP17A1 [11][12][13][14][15][16][17][18][19][20] as well as the interaction effects (epistasis) among them [15,21]. A summary of the principal studies about the genetic component of GI is shown in Table 1.…”
Section: The Genetic Componentmentioning
confidence: 99%
“…Paralleling the brain structural research, studies have been searching for a genetic component of GI. Some authors found variations in the DNA sequence of the androgen (AR) and estrogen (ERs, α and β) ( Henningsson et al, 2005 ; Hare et al, 2009 ; Fernández et al, 2014a , b , 2016 , 2018 , 2020a ; Cortés-Cortés et al, 2017 ; Foreman et al, 2019 ) that could hypothetically modulate the sensitivity of the nuclear steroid receptors. Furthermore, since AR and ER (α and β) are, at the same time, hormonal receptors and transcription factors, the modulation of gene expression via activation of AR and ERs by their ligands and coactivators, could be another presumptive mechanism underlying GI ( Fernández et al, 2021 ; Ramírez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%